Pigmented Villonodular Synovitis of the Temporomandibular Joint: A Report of Two Cases - Church, Christopher A.; Rowe, Mark; Llaurado, Raymund; Liwnicz, Boleslaw H.; Martin, Paul A. (Ear, nose, & throat journal, 2003)
Pigmented villonodular synovitis is a benign but locally destructive disease that originates in the synovial membranes of the joints. It is a proliferative disorder of unknown etiology, and it is usually monarthric. Approximately 80% of cases involve the knee; the hip, ankle, foot, hand, elbow, and shoulder account for most other cases. Pigmented villonodular synovitis in the temporomandibular joint is rare. When it does occur, its features include preauricular swelling, trismus, and symptoms of temporomandibular joint dysfunction. It can be diagnosed by a combination of the history, clinical examination, characteristic radiologic findings, and fine-needle aspiration or biopsy results. Wide local excision, including the involved bone, and a total synovectomy are advocated because the lesion can recur if it is not adequately excised. We report two new cases of pigmented villonodular synovitis of the temporomandibular joint, and we review the literature on this subject.